2002
DOI: 10.1038/sj.gene.6363813
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytokine mRNA levels in attack-free patients with familial Mediterranean fever

Abstract: Familial Mediterranean fever (FMF) is a recessively inherited inflammatory disorder, characterized by recurrent attacks of fever and serositis. Screening of mutations in the causing gene (MEFV) now allows accurate diagnosis of FMF among other inflammatory conditions. It is well documented that secreted levels of some pro-inflammatory cytokinesFamilial Mediterranean fever (FMF) is the prototype of a group of hereditary inflammatory disorders. Patients experience short, self resolving, attacks of fever and seros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 15 publications
3
32
0
5
Order By: Relevance
“…IL-6 and IL-8 are also increased during episode-free period. Although their levels are decreased under the treatment with colchicine, the transcription rates remain unchanged (54,(62)(63). In addition, IL-10, IL-12, IL-17 and IL-18 were also reported to increase during episode-free period.…”
Section: Fmf and Clinical-subclinical Inflammationmentioning
confidence: 93%
“…IL-6 and IL-8 are also increased during episode-free period. Although their levels are decreased under the treatment with colchicine, the transcription rates remain unchanged (54,(62)(63). In addition, IL-10, IL-12, IL-17 and IL-18 were also reported to increase during episode-free period.…”
Section: Fmf and Clinical-subclinical Inflammationmentioning
confidence: 93%
“…30 Moreover, attack-free periods of FMF are characterized by subclinical inflammation. 10,11 It was shown that serum IL-17 and IL-18 levels of FMF patients are higher than healthy controls both during acute phase and attack-free period.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nature of this regulation is not revealed precisely, pyrin, within a complex called inflammasome, serves as a regulator of the conversion of pro-interleukin (IL)-1b to mature IL-1b. 6,7 During inflammation episodes, neutrophils migrate into serous cavities and the levels of acutephase inflammatory products, including serum amyloid A and C reactive protein, 8 and cytokines including IL-6, 9,10 IL-8, 10 IL-17 11 and IL-18 11,12 increase. Besides these findings, it has been reported that substantial subclinical inflammation occurs during attack-free periods in patients with FMF and oxidative stress and oxidant/antioxidant imbalance might play a role in this persistent subclinical inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Buna karşın 1997'de yayınlanan bir başka çalışmada İL-6 ve İL-8 düzeylerinin FMF hastalarında atak dö-nemlerinde ataksız döneme göre yüksek olduğu bulunmuştur fakat istatiksel fark saptanmamıştır (23). İlginç olarak çok kısa süre önce yayınlanan bir çalışmada ise FMF hastalarının atak dışı dö-nemlerinde bakılan İL-1b, İL-6 ve İL-8 düzeyleri-nin sağlıklı kontrollerden yüksek olduğu saptanmış ve bunun da FMF hastalarında olduğu düşü-nülen subklinik inflamasyonun kanıtı olduğu belirtilmiştir (24).…”
unclassified